1991
DOI: 10.1128/aem.57.3.678-685.1991
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of Degradable Plastic Polyethylene by Phanerochaete and Streptomyces Species

Abstract: The ability of lignin-degrading microorganisms to attack degradable plastics was investigated in pure shake flask culture studies. The degradable plastic used in this study was produced commercially by using the Archer-Daniels-Midland POLYCLEAN masterbatch and contained pro-oxidant and 6% starch. The known lignin-degrading bacteria Streptomyces viridosporus T7A, S. badius 252, and S. setonii 75Vi2 and fungus Phanerochaete chrysosporium were used. Pro-oxidant activity was accelerated by placing a sheet of plast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
85
0
7

Year Published

1992
1992
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 287 publications
(104 citation statements)
references
References 14 publications
5
85
0
7
Order By: Relevance
“…Degradation of starch-filled polyethylene films has been reported by many researchers (Lee et al, 1991;Gould et al, 1990;Cole, 1990;Gage, 1990). Lee et al (1991) reported degradation of polyethylene molecules by lignindegrading bacteria in those films containing starch and prooxidant. Because of its hydrophilic properties, starch incorporation may, however, introduce undesirable properties into polyethylene film.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Degradation of starch-filled polyethylene films has been reported by many researchers (Lee et al, 1991;Gould et al, 1990;Cole, 1990;Gage, 1990). Lee et al (1991) reported degradation of polyethylene molecules by lignindegrading bacteria in those films containing starch and prooxidant. Because of its hydrophilic properties, starch incorporation may, however, introduce undesirable properties into polyethylene film.…”
Section: Introductionmentioning
confidence: 87%
“…Starch incorporation produces a plastic film with a porous structure, which enhances the accessibility of the plastic molecules to oxygen and microorganisms (Griffin, 1974). Degradation of starch-filled polyethylene films has been reported by many researchers (Lee et al, 1991;Gould et al, 1990;Cole, 1990;Gage, 1990). Lee et al (1991) reported degradation of polyethylene molecules by lignindegrading bacteria in those films containing starch and prooxidant.…”
Section: Introductionmentioning
confidence: 99%
“…Production of lignin peroxidases and Mn(I1) peroxidases was observed during these experiments (Milstein et al, 1992). Polyethylene containing 6% starch was incubated with P. chrysosporium in another study (Lee et al, 1991). The fungus did not degrade polyethylene, but this may have been due to the high nitrogen content of the medium used, which is known to inhibit the ligninolytic system of most whiterot fungi.…”
Section: Modified Polymersmentioning
confidence: 84%
“…Thermal oxidation of polyethylene is mainly carried out at temperatures ranging from 45 ∘ C to 150 ∘ C and generally characterized by lower temperatures with the longer time periods and higher temperatures with the shorter time periods. [3][4][5] For photo-oxidation, irradiation of polyethylene by UV is generally carried out at a temperature above 50 ∘ C. [6][7][8] The rate of polyethylene accumulation in nature is increasing each and every year and under this situation, faster and more effective methods of polyethylene removal must be found. Research has been carried out to increase the rate of biodegradation by increasing the extent of polyethylene oxidation and by using effective microbial species for polyethylene biodegradation.…”
Section: Introductionmentioning
confidence: 99%